The child care arrangements of working mothers with preschool aged children - Alcantara, Miriam C.
Eighty-eight working mothers wwith preschool aged children, from Kaingin1 in Quezon City and Bagong Pook and Banaybany in Lipa, Batangas, together with their care givers were interviewed about the details of their child care arrangements. Data obtained from these interviews were subjected either to the X2 or the Fisher Test to determine if certain family characteristics (household composition, maternal education, paternal education, maternal employment, paternal employment, fmily income number and ages of children in the family and location of residence) were significantly related to the mother's choices of actual and desired child care arrangements. The statistical tests showed that the rural mothers' actual child care arrangements were significantly related to their educational attainment and the number of children in their families while the desired child care arrangements were significantly related only to their educational attainment. No relationship was established between any of the urban mothers' child care arrangements and their family characteristics. The other pieces of information derived from the interviews were subjected to percentage computations.